Phonological Analysis of University Students’ Spoken Discourse - Clara Herlina (Bina Nusantara University, 2011)
The study of discourse is the study of using language in actual use. In this article, the writer is trying to investigate the phonological features, either segmental or supra-segmental, in the spoken discourse of Indonesian university students. The data were taken from the recordings of 15 conversations by 30 students of Bina Nusantara University who are taking English Entrant subject (TOEFL –IBT). Finally, the writer is in opinion that the students are still influenced by their first language in their spoken discourse. This results in English with Indonesian accent. Even though it does not cause misunderstanding at the moment, this may become problematic if they have to communicate in the real world.